Reactivity enhancement of lithium orthosilicate for thermochemical energy storage material usage. (December 2017) - Takasu, Hiroki; Kato, Yukitaka
Abstract: Recently, the advanced high temperature gas-cooled reactor (HTGR) was developed, and is recognized worldwide as a superior next-generation system due to its inherent safety and low environmental impact. Moreover, integrating thermal energy storage with HTGR can provide additional, more flexible options for meeting energy needs. Thermochemical energy storage (TcES) has several advantages, consequently, development of a TcES system for HTGR is desirable. The lithium orthosilicate/carbon dioxide reaction system (Li4 SiO4 /CO2 ) is one candidate which can be used at 800 °C. In this work, effects of potassium carbonate (K2 CO3 ) as an additive to Li4 SiO4 /CO2 were focused on and investigated.